The Development of Ecosystem Module Based on Science Literacy in Senior High School (Journal of Innovative Science Education, 2019)
Ecosystem materials taught with contextual examples need to be arranged in a type of teaching material for students. One teaching material that can be used is a module. Modules can be used by students with or without teacher guidance. so that students more easily understand material that is close to their daily lives. This study aims to analyze the effectiveness of the module on learning outcomes and students' scientific literacy abilities. as well as the module development response for teachers and students. This study used a pre-experimental method with the design of one group pretest-posttest design. Based on the results of the ecosystem module research based on scientific literacy effectively increasing student learning outcomes seen from the value of n-gain 0.70 in class X MIA 1 and 0.73 in class X MIA 2 with each criterion high. Effective module on the value of scientific literacy of students with a value of 84.15 in class X MIA 1 and 84.79 in class X MIA 2. Teacher responses to ecosystem modules based on scientific literacy results of 91.30%development of highly feasible criteria and student responses to ecosystem modules science-based literacy results of 85.50% development criteria are very feasible.